The Role of Digital Transformation in Business Model Innovation and Organizational Performance - Nurbaity Nurbaity; Riski Wahdini; Windy Septia; Dariari Robert (ADI Publisher, 2026)
This abstract is developed with a background that the rapid advancement of digital technologies has compelled organizations to pursue digital transformation as a strategic response to increasingly dynamic and complex competition, requiring sustainable business model innovation to enhance organizational performance. The Object of this study is to examine the role of digital transformation in driving business model innovation and its impact on organizational performance, with a focus on identifying key factors influencing the effectiveness of the transformation. The Method employed is a qualitative approach through a systematic literature review of internationally reputable Scopus-indexed journal articles published between 2021 and 2025, analyzed using thematic analysis to identify patterns, strategies, and relationships among digital transformation, business model innovation, and organizational performance. The Result indicates that digital transformation significantly fosters business model innovation through the utilization of digital platforms, big data, and artificial intelligence, which in turn positively impacts organizational performance, including operational efficiency, decision-making quality, and customer satisfaction. The study also finds that leadership, employee digital capabilities, and an adaptive organizational culture are key determinants of successful digital transformation. The Conclusion emphasizes that digital transformation is not merely a technological tool but an integral strategy that strengthens business model innovation and enhances organizational performance, making it a strategic necessity for companies in navigating the evolving digital economy.